2019
DOI: 10.1016/j.foodcont.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater conservation and reuse in quality vegetable cultivation: Overview, challenges and future prospects

Abstract: The serious water scarcity experienced across the globe and the desire for sufficient food production all year round to combat hunger, poverty and malnutrition necessitate the need for wastewater reuse in irrigation. Wastewater has varied compositions that affect the growth of different crops positively, they may also be a source of dangerous pollutant. Heavy consumption of vegetables have been encouraged for its nutritional and health advantages. Hence, their production and cultivation have increased globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 131 publications
(136 reference statements)
0
17
0
3
Order By: Relevance
“…For example, the set of projections for scenario methods while being used for landscaping and environmental goals, especially in areas suffering from water scarcity in the spring and summer seasons [23][24][25]. However, amongst financial constraints, inadequate regulatory frameworks, or engineering issues, several drawbacks mainly associated with health risks and significant sources of pollution to natural water bodies and the environment at large have increased the yuck factor [26,27]. For example, many studies have examined the role that factors such as water source, intended use, risk perception, trust, disgust, or economic incentives can have in hindering or facilitating acceptance of wastewater reuse.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the set of projections for scenario methods while being used for landscaping and environmental goals, especially in areas suffering from water scarcity in the spring and summer seasons [23][24][25]. However, amongst financial constraints, inadequate regulatory frameworks, or engineering issues, several drawbacks mainly associated with health risks and significant sources of pollution to natural water bodies and the environment at large have increased the yuck factor [26,27]. For example, many studies have examined the role that factors such as water source, intended use, risk perception, trust, disgust, or economic incentives can have in hindering or facilitating acceptance of wastewater reuse.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have confirmed that rain harvesting (RH) can provide water in urban/suburban, industrial, and rural areas [107][108][109][110][111][112][113][114][115][116][117][118], promising to save freshwater, a potential that may reduce tensions and competition among users. It is considered a low health risk, cost-efficient, and an environmentally friendly technology [119][120][121], a fact that has allowed its expansion in many developing and developed countries (EU, USA, UK, Japan, South Korea, Australia, and Africa) [116].…”
Section: Use Of Non-conventional Water Resources As a Means To Mitigate Water Competitions And Conflictsmentioning
confidence: 99%
“…In Europe, policies demanding proper treatment of wastewater before use for agricultural purposes are in place (Deviller et al, 2020). Wastewater irrigation exposed agricultural soil to many forms of contaminants including dangerous HMs (Chaoua et al, 2019;Inyinbor et al, 2019), pathogens, and soil salinization (Ofori et al, 2021). Wastewater contains more HMs than water from the canal and tube-well (Anjum et al, 2021).…”
Section: Waste Water Irrigationmentioning
confidence: 99%
“…Many farmers understand the dangers of using contaminated water in food production (Maleksaeidi et al, 2018) but have no concern about the consequences of their activities on the soil and water safety and humans health (Shaharoona et al, 2019). Water scarcity, poverty, and the pressing need for sufficient food production necessitate the use of contaminated water in food production (Inyinbor et al, 2019;Turan et al, 2018). Many farmers opt to use contaminated water because is the only available source they can afford (Maleksaeidi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%